Chemical profile and bioactivity of Chilean bean landraces (Phaseolus vulgaris L.). (May 2023) - Nina, Nélida; Theoduloz, Cristina; Paillán, Hernán; Jiménez-Aspee, Felipe; Márquez, Katherine; Schuster, Katharina; Becker, Laura; Oellig, Claudia; Frank, Jan; Schmeda-Hirschmann, Guillermo
Graphical abstract: Highlights: Antioxidant capacity and enzyme inhibition of beans before and after boiling. 43 constituents identified by HPLC-MS/MS analysis including phenolics and saponins. Cooking increased the ferulic acid and soyasaponins Ba and Bb contents. PCA analysis showed two classes of samples according to composition and seed color. Abstract: Beans ( Phaseolus vulgaris L.) are a traditional food in Chile. This work aimed to determine the chemical composition, antioxidant capacity, and enzyme inhibition effect of secondary metabolites-enriched extracts (SMEE) of thirteen Chilean bean landraces before and after boiling. The SMEE composition was assessed by HPLC-DAD-MS/MS, and the main compounds were quantified. Forty-three constituents were identified, including procyanidins, flavonoids, phenylpropanoids, and saponins. The chemical profiles, antioxidant and enzyme inhibition towards α-glucosidase allowed the differentiation of the samples into whole beans with lower and high phenolic and saponin contents. Cooking decreases the total phenolics and saponins content but some individual compounds such as ferulic acid and soyasaponins Ba and Bb increases. A significant correlation was found between total phenolics and antioxidant activity. A correlation was observed between some saponins and α-glucosidase inhibition. The bean components might exert a local activity on the intestine preventing oxidation of other nutrients and modulating gastrointestinal enzymes.